Acquisition of Freezing Tolerance in Vaccinium macrocarpon Ait. Is a Multi-Factor Process Involving the Presence of an Ice Barrier at the Bud Base - Villouta, Camilo; Workmaster, Beth Ann; Livingston, David P.; Atucha, Amaya (Frontiers in Plant Science, 2022)
Bud freezing survival strategies have in common the presence of an ice barrier that impedes the propagation of lethally damaging ice from the stem into the internal structures of buds. Despite ice barriers’ essential role in buds freezing stress survival, the nature of ice barriers in woody plants is not well understood. High-definition thermal recordings of Vaccinium macrocarpon Ait buds explored the presence of an ice barrier at the bud base in September, January, and May. Light and confocal microscopy were used to evaluate the ice barrier region anatomy and cell wall composition related to their freezing tolerance. Buds had a temporal ice barrier at the bud base in September and January, although buds were only freezing tolerant in January. Incomplete differentiation of vascular tissues may contribute to the impedance of ice propagation. Pith tissue at the bud base had comparatively high levels of de-methyl-esterified homogalacturonan, which may also block ice propagation. By May, the ice barrier was absent, xylogenesis had resumed, and de-methyl-esterified homogalacturonan reached its lowest levels, translating into a loss of freezing tolerance. The structural components of the barrier had a constitutive nature, resulting in an asynchronous development of freezing tolerance between anatomical and metabolic adaptations.